Valproic Acid-induced Priapism In A Child - Esra Türe; Abdullah Yazar; Fatih Akın; Ahmet Osman Kılıç (The Journal of Pediatric Academy, 2021)
A complete or partial involuntary erection that occurs in absence of a sexual stimulation and lasts longer than four hours is defined as priapism. Etiology usually includes sickle cell disease or hematologic malignancies. Less common causes include trauma, spinal cord injury, medications, congenital syphilis, parotitis, Fabry’s disease and retroperitoneal sarcoma. Priapism is a urologic emergency that varies by ischemic and non-ischemic episodes. Ischemic injury to cavernous tissues leads to erectile dysfunction. Early recognition of priapism, determination of the type and the treatment are crucial in preventing potential long-term complications caused by priapism.